Corporate governance and capital groups in Poland - Maria Aggestam (Journal for East European Management Studies, 2004)
The process of systemic change in Poland has brought about major changes in corporate governance. The enforcement of new laws has created a culture of compliance that has shaped capital groups and the management ethos of the groups, spurring them to improve. It is argued that the Polish versions of capital groups are markedly different from their western counterparts as they reflect unique historical patterns and socio-economic environments. The purpose of this paper is to discuss governance structures within capital groups from their transformation, institutionalization contingencies. Describing current forms of capital groups, the focus is on governance issues illustrated by two capital groups. Building on the Weimer/Pape (1999) framework, a taxonomy is proposed which contrasts governance in Poland with other economic systems. The paper concludes with preliminary theses about trends and current challenges for governing capital groups. – – Der Prozess des Systemwechsels in Polen hat viele grosse Veränderungen in Corporate Governance mit sich gebracht. Das Inkrafttreten neuer Gesetze schuf eine Kultur der Nachgiebigkeit, die die Vermögensgruppen und die Managementethik dieser Grupen formte und sie zur Verbesserung anspornte. Es wird behauptet, dass polnische Kapitalgruppen aufgrund ihres historischen Hintergrundes und sozioökonomischen Umfelds sich von ihren Pendants im Westen unterscheiden würden. Der Aufsatz diskutiert Strukturen von Corporate Governance innerhalb Kapitalgruppen anhand der Transformation und Institutionalisierung Aktuelle Formen der Kapitalgruppen werden beschrieben, der Fokus liegt jedoch auf Führungsfragen, die anhand zweier Kaputalgruppen erläutert werden. Basierend auf dem System von Weimer/Pope (1999) wird eine Taxonomie vorgeschlagen, die die Führung in Polen anderen Wirtschaftssystemen gegenüberstellt. Der Aufsatz schliesst mit vorläufigen Thesen über Trends und aktuelle Herausforderungen für Kapitalgruppen ab.
Keywords: 650; Corporate Governance; capital groups; transition economy; Poland